Immediate postoperative non‐invasive positive pressure ventilation following midface microvascular free flap reconstruction. Issue 7 (27th October 2021) - Larson, Andrew R.; Chen, Jenny X.; Holman, Allison; Sullivan, Stacey; Williams, Purris; Nicholson, Katharine; Lin, Derrick T.; Kiyota, Yuka; Richmon, Jeremy D.
Abstract: Background: There is a rare need for postoperative non‐invasive positive pressure ventilation (NIPPV) following microvascular reconstruction of the head and neck. In midface reconstruction, the free flap vascular pedicle is especially vulnerable to the compressive forces of positive pressure delivery. Case: A 60 year old female with Amyotrophic Lateral Sclerosis (ALS) presented with squamous cell carcinoma of the anterior maxilla, for which she underwent infrastructure maxillectomy and fibula free flap reconstruction. To avoid tracheotomy, the patient was extubated postoperatively and transitioned to NIPPV immediately utilizing a full‐face positive pressure mask with a soft and flexible sealing layer. The patient was successfully transitioned to NIPPV immediately after extubation. The free flap exhibited no signs of vascular compromise postoperatively, and healed very well. Conclusion: Postoperative non‐invasive positive pressure ventilation can be successfully applied following complex microvascular midface reconstruction to avoid tracheotomy in select patients without vascular compromise of the free flap.